Food insecurity, food based coping strategies and suboptimal dietary practices of adolescents in Jimma zone Southwest Ethiopia. - Tefera Belachew (Public Library of Science (PLoS), 2013)
Despite the high prevalence of adolescent food insecurity in Ethiopia, there is no study which documented its association with suboptimal dietary practices. The objective of this study is to determine the association between adolescent food insecurity and dietary practices. We used data on 2084 adolescents in the age group of 13-17 years involved in the first round survey of the five year longitudinal family study in Southwest Ethiopia. Adolescents were selected using residence stratified random sampling methods. Food insecurity was measured using scales validated in developing countries. Dietary practices were measured using dietary diversity score, food variety score and frequency of consuming animal source food. Multivariable regression models were used to compare dietary behaviors by food security status after controlling for socio-demographic and economic covariates. Food insecure adolescents had low dietary diversity score (P<0.001), low mean food variety score (P<0.001) and low frequency of consuming animal source foods (P<0.001). After adjusting for other variables in a multivariable logistic regression model, adolescent food insecurity (P<0.001) and rural residence (P<0.001) were negatively associated with the likelihood of having a diversified diet (P<0.001) and frequency of consuming animal source foods, while a high household income tertile was positively associated. Similarly, multivariable linear regression model showed that adolescent food insecurity was negatively associated with food variety score, while residence in semi-urban areas (P<0.001), in urban areas (P<0.001) and high household income tertile (P = 0.013) were positively associated. Girls were less likely to have diversified diet (P = 0.001) compared with boys. Our findings suggest that food insecurity has negative consequence on optimal dietary intake of adolescents. Food security interventions should look into ways of targeting adolescents to mitigate these dietary consequences and provide alternative strategies to improve dietary quality of adolescents in Southwest Ethiopia.